Edukasi Ukhuwah vs Flexing di bulan Puasa dan menjelang Idulfitri bagi Generasi Z - M. Rozali; Rismayanti Rismayanti; Larasati Nur Kharomah; Arya Prandana (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Ramadan and Eid al-Fitr, originally sacred moments for strengthening ukhuwah (brotherhood) and fostering self-restraint, are currently facing a shift in meaning due to the rise of "flexing" culture and hedonistic lifestyles on social media. This phenomenon of displaying wealth and achievements not only undermines the spiritual essence of worship through riya’ (showing off) and takabbur (arrogance) but also triggers negative psychological impacts such as insecurity and FOMO among the younger generation. This community service program, conducted at SMA Negeri 2 Medan, utilizes the Participatory Action Research (PAR) approach to address these moral challenges. Through participatory dialogue and collective case analysis, students are encouraged to develop critical consciousness regarding digital influences. By integrating digital literacy based on akhlakul karimah (noble character) and Islamic principles such as zuhud (asceticism) and tawadhu’ (humility), this program aims to realign the orientation of the "day of victory" toward simplicity and sincerity. The results indicate that internalizing the essence of fasting as a means of self-control (imsak) can effectively transform digital behavior into a more ethical practice, ensuring that Eid al-Fitr remains a moment of spiritual triumph free from the stains of materialistic pride.